DOES ISLAMIC ENTREPRENEURSHIP ALIGNED WITH DIGITALIZATION ERA? - Rahmayanti, Ifada; Wardiyanta, Wardiyanta; Ikawati, Retty (Universitas Mercu Buana, 2023)
The purpose of this article is to explain several research gaps including: the assumption that occurs in society that entrepreneurship carried out Islamically is often not in line with the digitalization era. The view that Islamic entrepreneurship is the same as trading conventionally is still inherent in society. In addition, digital problems are not the main goal of Muslims. Therefore, how to align Islamic entrepreneurship with the era of digitalization needs to be investigated furtherThis study applies feasibility study with qualitative descriptive method. It is stated that problems that occur in society must be studied in certain situations, including regarding the relationship between events and SWOT analysis as a strategy, as well as the views that prevail in society. Because of such findings, the interjection using SWOT analyisis as a strategy resulted in an enlightenment, namely Islamic entrepreneurship can be in harmony with digital technology. The novelty of the study is important, namely that research with this title has not existed before. The discovery of the novelty of this research can be seen in figure namely Analysis SWOT Diagram for Islamic Entrepreneurship Alignment with Digital Era. For The implication that can be carried out is that this research can be a reference material not only for Muslim entrepreneurs but also general entrepreneurship that to advance their businesses must align with technology at that time.